2021
DOI: 10.1007/s00428-021-03152-z
|View full text |Cite|
|
Sign up to set email alerts
|

Keratin 7 expression in hepatic cholestatic diseases

Abstract: We evaluated keratin 7 (K7) hepatocellular expression in 92 patients with common types of acute and chronic cholestatic diseases caused by bile duct obstruction/destruction or parenchymal lesions [acute hepatitis (n=20), mixed/pure cholestasis (n=16), primary biliary cholangitis-PBC (n=35), primary sclerosing cholangitis-PSC (n=10), vanishing bile duct syndrome (n=3), complete large bile duct obstruction due to space-occupying lesions (n=8)]. K7 immunohistochemical hepatocellular expression and ductular reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…16 CK7 is a marker of cholangiocytes but has also been used to highlight cholestatic hepatocytes. 24,25 Studies have demonstrated that CK7 positive hepatocytes with or without pseudoacinar morphology in central areas of the FNH, suggesting chronic cholestasis is likely a common feature of FNH. 5,12,13,16,26 It is thought that the capacity of hepatocytes in FNH to take up bile acids from the blood and to secrete bile persists, but the lack of draining bile ducts and hepatocytic senescence may lead to increasing cholestasis, ductular reaction, and even pseudoacini formation.…”
Section: Discussionmentioning
confidence: 99%
“…16 CK7 is a marker of cholangiocytes but has also been used to highlight cholestatic hepatocytes. 24,25 Studies have demonstrated that CK7 positive hepatocytes with or without pseudoacinar morphology in central areas of the FNH, suggesting chronic cholestasis is likely a common feature of FNH. 5,12,13,16,26 It is thought that the capacity of hepatocytes in FNH to take up bile acids from the blood and to secrete bile persists, but the lack of draining bile ducts and hepatocytic senescence may lead to increasing cholestasis, ductular reaction, and even pseudoacini formation.…”
Section: Discussionmentioning
confidence: 99%
“…Keratins and other intermediate filaments are cytoprotective proteins and reportedly upregulated in various stress and regenerative conditions, which may explain the here described K7 neo-expression in the colonic epithelium of IBD patients 8 , 32 . Simple epithelial keratins including K7 have been shown to be upregulated or neo-expressed in patients and in mouse disease models, for example in kidney epithelial cells during renal injury 33 , in β-cells after diabetes induction 34 , and in hepatocytes of patients with cholestatic diseases 35 . Similarly, in mouse models of colonic stress and inflammation, simple epithelial keratins were upregulated, including K7 which was increased in a model of chronic colitis and in aging mice 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Many histopathological examinations have reported the expression of the BEC marker KRT7 in hepatocytes during cholangiopathies. [36][37][38][39][40][41][42] In cases of Alagille syndrome as well as biliary atresia, the number of IHBCs co-expressing the BEC markers KRT7 or HNF6 and the hepatocyte markers LKM-1, BSEP, or HNF4a is significantly increased. 43 In both primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC), the appearance of IHBCs increases with the stage of fibrotic damage to the tissue.…”
Section: Evidence Of Hepatobiliary Plasticity In Humansmentioning
confidence: 99%